Bioreactance reliably detects preload responsiveness by the end-expiratory occlusion test when averaging and refresh times are shortened - Francesco Gavelli; Alexandra Beurton; Jean-Louis Teboul; Nello De Vita; Danila Azzolina; Rui Shi; Arthur Pavot; Xavier Monnet (Annals of Intensive Care, 2021)
Abstract Background The end-expiratory occlusion (EEXPO) test detects preload responsiveness, but it is 15 s long and induces small changes in cardiac index (CI). It is doubtful whether the Starling bioreactance device, which averages CI over 24 s and refreshes the displayed value every 4 s (Starling-24.4), can detect the EEXPO-induced changes in CI (ΔCI). Our primary goal was to test whether this Starling device version detects preload responsiveness through EEXPO. We also tested whether shortening the averaging and refresh times to 8 s and one second, respectively, (Starling-8.1) improves the accuracy of the device in detecting preload responsiveness using EEXPO. Methods In 42 mechanically ventilated patients, during a 15-s EEXPO, we measured ∆CI through calibrated pulse contour analysis (CIpulse, PiCCO2 device) and using the Starling device. For the latter, we considered both CIStarling-24.4 from the commercial version and CIStarling-8.1 derived from the raw data. For relative ∆CIStarling-24.4 and ∆CIStarling-8.1 during EEXPO, we calculated the area under the receiver operating characteristic curve (AUROC) to detect preload responsiveness, defined as an increase in CIpulse ≥ 10% during passive leg raising (PLR). For both methods, the correlation coefficient vs. ∆CIpulse was calculated. Results Twenty-six patients were preload responders and sixteen non preload-responders. The AUROC for ∆CIStarling-24.4 was significantly lower compared to ∆CIStarling-8.1 (0.680 ± 0.086 vs. 0.899 ± 0.049, respectively; p = 0.027). A significant correlation was observed between ∆CIStarling-8.1 and ∆CIpulse (r = 0.42; p = 0.009), but not between ∆CIStarling-24.4 and ∆CIpulse. During PLR, both ∆CIStarling-24.4 and ∆CIStarling-8.1 reliably detected preload responsiveness. Conclusions Shortening the averaging and refresh times of the bioreactance signal to 8 s and one second, respectively, increases the reliability of the Starling device in detection of EEXPO-induced ∆CI. Trial registration: No. IDRCB:2018-A02825-50. Registered 13 December 2018.